MEDIA TANAMORGANIK DAN POSISI TANAM BENIH PENGARUHNYA TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (COFFEA CANEPHORA ) - ANAK AGUNG GEDE PUTRA; PANDE GEDE GUNAMANTA; KETUT TURAINI INDRA WINTEN (Universitas Mahasaraswati Mataram, 2020)
The study aimed to determine the effect of organic planting media and the position of seed planting on the growth of Robusta coffee seedlings. The study is conducted at the Tabanan Agrotechnology Study Program, Tabanan University, which conducted from July 2019 to September 2019. The treatments are arranged in factorial in a randomized block design (RBD). Two treatments examined in this study were the doses of organic matter in the growing media (0g, 150 g, 300 g, 450 g) and seed position (prone position, upside down, tilted position). The results show that the interaction between organic planting media (soil + coffee leaf compost) and seed planting position did not significantly affect all coffee seedlings growth variables. The dose of organic compost in the growing media has a very significant effect on all growth variables except when growing and the percentage of growth. The dosing of 450 g organic matter gave the highest root fresh weight, fresh stem weight and fresh leaf weight (1.00 g, 2.97 g and 8.64 g respectively) and oven dry weight for the three variables (respectively 0.39 g, 0.55 g and 1.36 g). Seed planting position has no significant effect on all observed variables, but there is The tendency of planting position with the prone on average gives better growth compared to other positions.